2019
DOI: 10.1101/608976
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective Prespacer Processing Ensures Precise CRISPR-Cas Adaptation

Abstract: CRISPR-Cas immunity protects prokaryotes against foreign genetic elements. CRISPR-Cas uses the highly conserved Cas1-Cas2 complex to establish inheritable memory (spacers). It remains elusive how Cas1-Cas2 acquires spacers from cellular DNA fragments (prespacers) and how it integrates them into the CRISPR array in the correct orientation. By using the high spatiotemporal resolution of single-molecule fluorescence, we reveal that Cas1-Cas2 obtains prespacers in various forms including single-stranded DNA and pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…For example, spacer acquisition in the E. coli Type I-E system requires the integration host factor protein to bend the leader, which sequesters the promoter and most likely shuts off transcription 18 . An integral component of the DNA replisome, DnaJ, is further required to nucleolytically process the PAM-side of the prespacer to complete full-integration 49 . The PSC resolution in this subset of the CRISPR systems may indeed be replication-coupled; however, the coupling does not always take place in a timely fashion, as a small percentage of the E. coli spacers appear to have been acquired from disintegrated prespacer reintegrated in the wrong orientation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, spacer acquisition in the E. coli Type I-E system requires the integration host factor protein to bend the leader, which sequesters the promoter and most likely shuts off transcription 18 . An integral component of the DNA replisome, DnaJ, is further required to nucleolytically process the PAM-side of the prespacer to complete full-integration 49 . The PSC resolution in this subset of the CRISPR systems may indeed be replication-coupled; however, the coupling does not always take place in a timely fashion, as a small percentage of the E. coli spacers appear to have been acquired from disintegrated prespacer reintegrated in the wrong orientation 37 .…”
Section: Discussionmentioning
confidence: 99%
“…2). Moreover, a parallel study on prespacer generation in E. coli also independently demonstrated that the generic nucleases (such as DNA polymerase III or exonuclease T) are sufficient for trimming the prespacers upon PAM recognition by Cas1-2 (74). These explain why the involvement of specific nucleases, such as Cas4, is precluded for prespacer processing in E. coli (see below).…”
Section: Mechanism Of Prespacer Capture and Processing In E Colimentioning
confidence: 95%